2019
DOI: 10.5812/ijhrba.66232
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Mortality of Burn Injuries in Eastern Iran Since 2009: An analysis of 2115 Cases

Abstract: Background: Historically, burn injuries have been accompanied by bad prognosis. With the advances in recovering fluids and the early excision of burn scars, the survival rate has enhanced for severe burn patients. Objectives:The study aimed to analyze the epidemiology of burn injuries in Zahedan, Eastern Iran. Patients and Methods: This retrospective study examined 2173 burn patients for eight years. The research data were extracted from patients' files and analyzed by SPSS 22 using the chi square test, t test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…They concluded that further studies are needed to identify preventive strategies for reducing the risk of selfimmolation, such as consultation and instructional courses during the high school years. 14 Nazeer et al reported that lethality was higher in patients with self-immolation. Also, this method of suicide was a highly lethal method.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that further studies are needed to identify preventive strategies for reducing the risk of selfimmolation, such as consultation and instructional courses during the high school years. 14 Nazeer et al reported that lethality was higher in patients with self-immolation. Also, this method of suicide was a highly lethal method.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic search identi ed seventeen studies containing epidemiological characteristics of burn injuries in Iran with a total number of 61662 patients. The included articles consisted of studies conducted in ten provinces of Iran (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and one study based on the national burn registry in Iran. (34) A ow diagram illustrating the literature search and study selection is shown in Fig.…”
Section: Systematic Searchmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Burns can be defined as damage to the skin or any organic tissue that is mainly caused by fire, electricity, radioactive, radiation, and chemical substances. [15][16][17][18][19][20][21][22][23][24] Burn injuries produce some of the most painful patient experiences [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and may result in unpleasant physical and psychological outcomes among patients. [41][42][43][44][45][46][47][48][49][50]…”
Section: Introductionmentioning
confidence: 99%